Innovation capabilities in the convergence trend of higher education from the perspective of quality management - Wu, Jingjing; Gu, Yixian (Frontiers in Psychology, 2022)
With changing trends and technology, the education system has evolved from a traditional to a modernized, qualitative, and innovatively sustained education system. Many factors contribute to process innovation and quality management benchmarks. This study has two primary goals: (1) determining the causal relationship between TQM and innovation capability, and (2) determining whether the exam, admission, and placement process have any effect on TQM and identifying whether TQM can act as a mediator between the admission, exam, and placement process and innovation capabilities. Furthermore, the study used TQM in multiple dimensions (quality management and leadership, staff interaction, institute productivity, control & measurement of processes). As a result, the current study is the only one to look at TQM with its specific dimensions as a mediator, specifically in higher education. The survey and correlational methods were chosen to test the theoretical framework established using resource-based theory and explicitly based on structural equation modeling using Partial Least Square. A structured questionnaire based on a five-point Likert scale was also distributed to 350 professors (faculty members) from Chinese universities to assess the research constructs. The findings revealed that TQM positively and significantly impacts innovation capabilities. Besides, the admission, exam, and placement process is inextricably linked to TQM’s dimensions and innovation capabilities. TQM also mediated significantly, and all hypotheses tested supported the findings. Future researchers should look into collaborative innovation capabilities and compare teachers’ innovation capabilities in higher education, according to the study.